2017
DOI: 10.3390/en10030342
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Periodic Fluctuations in Energy Efficiency in Centrifugal Pumps at Different Working Points

Abstract: Abstract:In order to simulate the energy efficiency fluctuation behavior of an industrial centrifugal pump with a six-blade impeller, a full-scale three-dimensional (3D) an unsteady state computational fluid dynamics (CFD) model was used. Five operational points with different flow fluxes were numerically investigated by using the Navier-Stokes code with shear-stress transport (SST) k-ω turbulence model. The predicted performance curves agreed well with the test data. A sine function was fitted to the transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A numerical study found that the volume flow rate of the leakage flow directly affected the liquid pressure in the balance chamber, and the calculation of the impeller cover plate force (i.e., the axial force of the centrifugal pump) and an appropriate balance hole diameter could balance the axial force to its maximum [9]. Other studies [10][11][12][13][14][15][16] found that the characteristics of leakage flow in the balance chamber directly influence the accuracy of the axial force prediction. Other studies [17,18] on the centrifugal pump have concluded that the distribution of axial velocity in the lateral chamber of the back cover plate is similar to that in the closed cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…A numerical study found that the volume flow rate of the leakage flow directly affected the liquid pressure in the balance chamber, and the calculation of the impeller cover plate force (i.e., the axial force of the centrifugal pump) and an appropriate balance hole diameter could balance the axial force to its maximum [9]. Other studies [10][11][12][13][14][15][16] found that the characteristics of leakage flow in the balance chamber directly influence the accuracy of the axial force prediction. Other studies [17,18] on the centrifugal pump have concluded that the distribution of axial velocity in the lateral chamber of the back cover plate is similar to that in the closed cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous work by Zhang et al [1,24,25], this research presents a new one-way coupling simulation approach for the flow-induced vibration of rotor assembly in centrifugal pump, with special attention on the association features of unsteady internal flow and shaft vibration. Compared with…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. 14 investigated the efficiency fluctuation in a centrifugal pump with six blades and argued that fluid was distributed unevenly and caused the periodic fluctuation when the discharge was larger than the optimal point.…”
Section: Introductionmentioning
confidence: 99%